PEMATANG PANTAI PURBA SEBAGAI PERANGKAP GAS BIOGENIK DI PESISIR INDRAMAYU PROVINSI JAWA BARAT SUATU KAJIAN PENDAHULUAN - Kurnio, H.; Naibaho, T. (Jurnal Geologi dan Sumberdaya Mineral, 2011)
Biogenic gas potency in Indramayu coastal area had been studied by coastal characteristic mapping, soft sediment sampling using specially designed gravity corer and information of gas seeps from local people. The preliminary study was carried out through gatherings of secondary data from many sources which meant to better understand the forms of paleo-dunes in coastal zone of Indramayu surround Cimanuk River deltaic system that already buried subsurface. The study found out that this alternative gas potency is trapped within paleo-beach sand in Indramayu coastal zone. The study also found that the buried beach sand at southeast of Cimanuk River delta's system parallel to northwest-southeast orientation of recent coastline is bearing biogenic gas potency. Based on field observation, the locations of gas seeps take place on the beach sand mentioned. The study also performed utilization of biogenic gas by community south of Indramayu.Key words: paleo-coastal dune, biogenic gas trap, Indramayu coastal zone.